The Sweden Ticket : An overview of the “German Ticket” and possibilities for a similar ticket in Sweden - Hagemann, Johannes; Johansson, Michael ; 0000-0002-9174-5408 (2025)
This paper examines the impact of Germany’s 9-Euro-Ticket and its successor, the German Ticket (49 €), on public transportation usage, environmental benefits, and social equity, while exploring the feasibility of implementing a similar model in Sweden. The 9-Euro-Ticket, introduced in 2022 as a temporary measure to alleviate economic strain from rising energy costs, significantly increased public transport ridership by 42%, reduced car usage by 16%, and saved 4.2–6.5 million tons of CO₂ emissions. Despite its success, the ticket disproportionately benefited higher-income groups and urban areas, underscoring infrastructure gaps in rural regions. The transition to the 49 € German Ticket maintained positive effects, with 14 million users by 2024, demonstrating sustained demand. Economically, the German Ticket generated a net benefit of at least 3 billion euros for society. This includes savings from reduced car traffic (2.37–3.69 billion €), lower CO₂-related damages (1.3–2 billion €), and a subsidy effect where users saved more than the state spent on compensation for transport providers. Dynamic effects, such as 1.34 million users considering car ownership unnecessary, further amplified long-term economic and environmental gains. For Sweden, Germany’s experience highlights the potential of affordable, unified public transport tickets to boost sustainability and equity. Key takeaways include the importance of stakeholder coordination, targeted rural investments, and pilot projects to assess feasibility. The success of Germany’s model suggests that similar initiatives could drive meaningful change in Sweden’s transport sector.